9 x square - 3 x minus 2
Answers
Answered by
4
Hey!!
![9x {}^{2} - 3x - 2 \\ \\ = > 9x {}^{2} - 6x + 3x - 2 \\ \\ = > 3x(3x - 2) + 1(3x - 2) \\ \\ = > (3x - 2)(3x + 1). 9x {}^{2} - 3x - 2 \\ \\ = > 9x {}^{2} - 6x + 3x - 2 \\ \\ = > 3x(3x - 2) + 1(3x - 2) \\ \\ = > (3x - 2)(3x + 1).](https://tex.z-dn.net/?f=9x+%7B%7D%5E%7B2%7D++-+3x++-++2+%5C%5C++%5C%5C++%3D++%26gt%3B+9x+%7B%7D%5E%7B2%7D++-+6x+%2B+3x++-++2+%5C%5C++%5C%5C++%3D++%26gt%3B+3x%283x+-+2%29+%2B+1%283x+-+2%29+%5C%5C++%5C%5C++%3D++%26gt%3B+%283x+-+2%29%283x+%2B+1%29.)
Hope it helps!
Hope it helps!
84nitusingh:
Rthh
Answered by
3
HOPE THIS HELPS YOU ❤❤❤
Similar questions
Science,
8 months ago
Math,
8 months ago
Computer Science,
1 year ago
Math,
1 year ago
Math,
1 year ago